Um aplicativo para auxiliar na alfabetização de indivíduos com autismo - Garcia, Pedro de Moura (2018)
There is a growing need to create new technologies that provide support in the education area. This need is even bigger when we deal with the literacy process of people with Autism Spectrum Disorder (ASD), where access to technology support and services is often inadequate. In this context, this paper introduces a mobile application denominated ABC Fônico, created with the purpose of assisting in literacy and in the construction of phonological awareness of people with autism. It presents as main characteristics the use of simple and adaptive interfaces to introduce the phonic alphabet, besides implementing structured games based on the TEACCH method. Preliminary results show that the application has good acceptance and understanding of the proposed activities and ease of use.